Inquisitorial: Menelusuri Titik Terminal Keberangkatan Ilmu Pemerintahan Di Indonesia - Gafar, T. Fahrul; Jamil, Zamhasari (ARISTO, 2018)
This research is a scientific effort to trace the historical footsteps of the birth, growth, and development of Government Science in Indonesia. The disclosure of the early phenomenon of science would certainly be the gateway in giving a pure understanding of that science. so that, the result of its inquiry can serve as one of the main sources/ references that provide complete and comprehensive information for further study of Government Science. This study used a qualitative approach with descriptive type and with the library research form. In this study, the researcher observed the object of research through literature materials so that the theories underlying the problems in the field under study can be clearly revealed. With the selection of approaches, types, and forms of research, will certainly be able to reveal in depth how the historical roots of Government Science and able to emphasize the locus / position of Government Science among other state sciences.